Performance of maize (Zea mays) genotypes in different ecological systems - Kumar, P; Godawat, S L; Vyas, Mukesh; Pandiya, N K (The Indian Journal of Agricultural Sciences, 2008)
Field experiments were conducted during 2004-05 at Udaipur to develop single cross hybrids with good combining inbred lines for semi-arid tropics. The single cross hybrids developed through crossing 10 elite inbred lines with drought-tolerant exotic testers, viz ’CML 341’ and ’Pool 16 BN’ in line x tester mating design, were evaluated under rainfed (kharif), normal irrigation and terminal drought (rabi) conditions. Hybrids (F1 s) exhibited higher grain yield, plant height and ear height along with earliness and narrow anthesis-silking interval over parental lines under varying ecological situations. The traits under investigation were governed by additive (s2A) and non-additive (s2D) gene actions and thus could be improved through selection, followed by hybridization. The good general combining inbreds with high per se performance for grain yield, earliness and various yield attributes were ’EI 570’ in rainfed; ’EI 572’ in normal irrigated, while ’EI 569’, ’EI 571’ and ’EI 573’ in terminal drought environment. Hybrid ’EI 573’ x ’Pool 16 BN’under every environment while hybrid ’EI 569’ x ’Pool 16 BN’ under normal irrigated and terminal moisture stress conditions express supremacy, since they exhibited higher estimates of specific combining ability effects, heterobeltiosis, economic heterosis and per se performance for grain yield and various yield attributes.